Reliability and validity of a new variable-power performance test in road cyclists - Sharma, A. P.; Elliott, A. D.; Bentley, D. J. (International Journal of Sports Physiology and Performance, 2015)
Context: Road cycle racing is characterized by significant variability in exercise intensity. Existing protocols attempting to model this aspect display inadequate variation in power output. Furthermore, the reliability of protocols representative of road cycle racing is not well known. There are also minimal data regarding the physiological parameters that best predict performance during variable-power cycling. Purpose: To determine the reliability of mean power output during a new test of variable-power cycling and establish the relationship between physiological attributes typically measured during an incremental exercise test and performance during the variable-power cycling test (VCT). Methods: Fifteen trained male cyclists (mean ± SD age 33 ± 6.5 y, VO2max 57.9 ± 4.8 mL/kg·min) performed an incremental exercise test to exhaustion for determination of physiological attributes, 2 VCTs (plus familiarization), and a 30-km time trial. The VCT was modeled on data from elite men`s road racing and included significant variation in power output. Results: Mean power output during the VCT showed good reliability (r = .92, CV% = 1.98). Relative power during the self-paced sections of the VCT was most correlated with maximal aerobic power (r = .79) and power at the second ventilatory threshold (r = .69). Blood lactate concentration showed poor reliability between trials (CV% = 13.93%). Conclusions: This study has demonstrated a new reliable protocol simulating the stochastic nature of road cycling races. Further research is needed to determine which factors predict performance during variable-power cycling and the validity of the test in monitoring longitudinal changes in cycling performance.